Phylogenetic and structural response of heterotrophic bacteria to dissolved organic matter of different chemical composition in a continuous culture study. (10th September 2013) - Landa, M.; Cottrell, M. T.; Kirchman, D. L.; Kaiser, K.; Medeiros, P. M.; Tremblay, L.; Batailler, N.; Caparros, J.; Catala, P.; Escoubeyrou, K.; Oriol, L.; Blain, S.; et al.
Summary Dissolved organic matter (DOM) and heterotrophic bacteria are highly diverse components of the ocean system, and their interactions are key in regulating the biogeochemical cycles of major elements. How chemical and phylogenetic diversity are linked remains largely unexplored to date. To investigate interactions between bacterial diversity and DOM, we followed the response of natural bacterial communities to two sources of phytoplankton‐derived DOM over six bacterial generation times in continuous cultures. Analyses of total hydrolysable neutral sugars and amino acids, and ultrahigh resolution mass spectrometry revealed large differences in the chemical composition of the two DOM sources. According to 454 pyrosequences of 16S ribosomal ribonucleic acid genes, diatom‐derived DOM sustained higher levels of bacterial richness, evenness and phylogenetic diversity than cyanobacteria‐derived DOM. These distinct community structures were, however, not associated with specific taxa. Grazing pressure affected bacterial community composition without changing the overall pattern of bacterial diversity levels set by DOM. Our results demonstrate that resource composition can shape several facets of bacterial diversity without influencing the phylogenetic composition of bacterial communities, suggesting functional redundancy at different taxonomic levels for the degradation of phytoplankton‐derived DOM.